ESAT-6-ELISpot and interferon γ in the diagnosis of pleural tuberculosis - Waheed Shouman; Mohamed El-Gammal; Amany Shaker; Ashraf El-Shoura; Ayman Marei; Mohammed El-Ahmady; Ghada Boghdadi (Egyptian Journal of Chest Disease and Tuberculosis, 2012)
Background: Appropriate diagnostic methods for tuberculous pleural effusion are vital. The IFN-γ tests using specific Mycobacterium Tuberculos is antigens in samples from the site of infection may be promising in diagnosis of tuberculosis. Objective we examined the ability of ELISpot test using circulating peripheral blood mononuclear cells (PBMC) and compartmentalized pleural fluid mononuclear cells (PFMC) for diagnosis of active TB infection in patients with tuberculous pleural effusion. Methods PBMC and PFMC-based ELISpot test for IFN-γ test using specific M. tuberculosis antigen: Early Secretory Antigen Target-6 protein (ESAT-6) was used for diagnosis of active TB infection. Thirty-five patients with clinically suspected tuberculous pleural effusion were enrolled over a 12-month period. Results 11 patients out of 35 were positive by culture and PCR (31.4%). Incubation of PBMC with ESAT-6 for 8 h showed sensitivity and specificity of 82% and 92%, respectively, for the PBMC–ELISpot as compared to PFMC–ELISpot that was 54% and 96% respectively. With 24 h incubation of ESAT-6 there was around 2.5 fold increase in the median number of spot forming cells (SFCs) in PFMC from 30 to 74, whereas there was minimal increase of median number of SFCs in PBMC from 55 to 60. Conclusion ESAT-6 – ELISpot using PBMC and PFMC is useful as a tool for diagnosis of TB effusion. PFMC needs longer period of incubation for processing of ESAT-6 than PBMC. Moreover, IFN-γ in pleural effusion (PE) is another useful way for diagnosis of TB pleurisy which is sensitive, simple and cheap.